The Role of Plant Origin Preparations and Phenological Stage in Anatomy Structure Changes in the Rhizogenesis of Rosa “Hurdal” - Monder, Marta Joanna; Kozakiewicz, Paweł; Jankowska, Agnieszka (Frontiers in Plant Science, 2021)
Most Old Roses are difficult to root when propagated by cuttings. This research focused on the response of stem cuttings of Rosa ‘Hurdal’ to plant origin preparations used as rhizogenesis enhancers through changes to the anatomical structure of the stem’s basal part. Cuttings derived from shoots in four phenological stages were prepared for the experiment: flower buds closed (H1); fully flowering (H2); immediately after petals have fallen (H3); 7-14 days after petals have fallen (H4). The cuttings were treated with 0.4% indolebutyric acid (IBA) or 0.2% naphthalene acetic acid (NAA), and with plant origin preparations: Algae extract, Organic preparation, Plant extract. A high rooting percentage in comparison to the control (27.5%) was obtained after treatments of the H1 cuttings with Algae extract (90%), Organic preparation (80%) and Plant extract (75%). The H4 cuttings did not root, probably as a result of overgrowing callus and limited of xylem formation. The anatomical structure of the shoot differed in subsequent phenological stages during the period of rooting in various ways, depending on the rooting enhancer used for treatment. Numerous correlations between rooting percentage and anatomical structure were proved, including the key role of vascular bundles in increasing rooting percentage by widening vessel diameter.